Maggot Black Soldier Fly Supplementation on Feed to Production Performance and Business Analysis Super Native Chicken Finisher Period - Fuddin, Muhammad Nazar; Lamid, Mirni; Al Arif, Mohammad Anam; Lokapirnasari, Widya Paramita; Hidanah, Sri; Sarmanu, Sarmanu (Universitas Airlangga, 2022)
This study aimed to determine the analysis of super native chicken farm business with Black Soldier Fly (BSF) maggot supplementation on feed on the production performance of super native chickens, including feed consumption, body weight gain and feed conversion. This study used 50 super male native chickens aged 4 weeks and adapted for 1 week then randomized into five treatments, including P0 (basal feed without BSF maggot), P1 (basal feed + 2.5% BSF maggot), P2 (basal feed + 5% BSF maggot), P3 (basal feed + 7.5% BSF maggot), and P4 (basal feed + 10% BSF maggot). Statistical data analysis was processed using One Way ANOVA and followed by post hoc Duncan. The results showed that the level of feed consumption was high in treatment P4, the highest body weight gain was in P4, the lowest feed conversion was in P1. Contribution margin analysis (CM) was used to determine the benefits of the treatment in this study. 2.5% BSF (P1) maggot supplementation is recommended to increase profits.